2019
DOI: 10.1039/c9ra01417a
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven locomotion of a centimeter-sized object at the air–water interface: effect of fluid resistance

Abstract: Centimeter-sized flat-headed push pin with photothermal properties can be moved on a water surface by a simple near-infrared laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Numerical analyses indicated that the maximum velocity and acceleration became smaller as the bubble size increased. This should be due to an increase of area of the bubble projected to the locomotion direction in water phase, where the bubbles experience greater resistance, compared to the air phase . Furthermore, the decay time became longer with an increase of bubble size.…”
Section: Results and Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Numerical analyses indicated that the maximum velocity and acceleration became smaller as the bubble size increased. This should be due to an increase of area of the bubble projected to the locomotion direction in water phase, where the bubbles experience greater resistance, compared to the air phase . Furthermore, the decay time became longer with an increase of bubble size.…”
Section: Results and Discussionmentioning
confidence: 98%
“…This should be due to an increase of area of the bubble projected to the locomotion direction in water phase, where the bubbles experience greater resistance, compared to the air phase. 54 Furthermore, the decay time became longer with an increase of bubble size. This is because the bubble mass is larger and, therefore, greater inertia was at work (see the next section).…”
Section: ■ Experimental Sectionmentioning
confidence: 98%
“…S8), and μ is the kinematic viscosity of water. The Re is calculated to be 22.9 to 33.8 (laminar flow state), so the c can be approximated as the friction drag coefficient for laminar flow ( c = 1.328 Re −1/2 ) ( 47 , 48 ). The fluid resistance f is calculated to be 0.073 to 0.13 μN, which is in accordance with the magnitude of the maximum phenomenological resistance (0.071 to 0.093 μN).…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, there has been an increasing interest in active matters, by constructing and controlling substances or composite systems that exhibit chemically driven self-propulsion. Such self-propelled systems are expected to have a wide range of applications, such as drug delivery systems, , sensors, and labor-saving pesticides. , In addition, self-propelled systems sometimes play key roles in collective behaviors as natural or artificial micromotors . At the millimeter or smaller size scale where these systems reside, the interfacial tension is often the dominant force.…”
Section: Introductionmentioning
confidence: 99%